2015
DOI: 10.1097/maj.0000000000000439
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Safety Profile and Clinical Experience With High-Dose Domperidone Therapy for Nausea and Vomiting

Abstract: Abstract:Introduction:Domperidone is a dopamine receptor antagonist with peripheral prokinetic and central antiemetic properties. Prolongation of the QTc interval with chronic use of oral domperidone in standard doses has been reported in the literature. Our goal was to investigate cardiac toxicity in patients receiving 2-fold greater doses than in previous reports.Methods:A retrospective chart review was conducted of patients with nausea (N) and vomiting (V) receiving domperidone from 2009 to 2013 under an In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
1
18

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 19 publications
0
60
1
18
Order By: Relevance
“…Other studies have shown improvement in gastroparesis symptoms with domperidone therapy . Symptoms that have been reported as improving include nausea, vomiting, postprandial fullness, and early satiety.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Other studies have shown improvement in gastroparesis symptoms with domperidone therapy . Symptoms that have been reported as improving include nausea, vomiting, postprandial fullness, and early satiety.…”
Section: Discussionmentioning
confidence: 96%
“…There is concern about domperidone prolonging the QTc on electrocardiograms and possibly predisoposing patients to arrhythmias. In a recent study of patients taking high dose domperidone for GI symptoms, 27% were found to have QTc prolongation . However, none of these patients experienced arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It will not produce bad effects on the central nervous system as it is difficult to enter the brain. Besides, it can selectively block dopamine 2 and mainly act on the peripheral nervous system 15. Domperidone can improve the power of digestive tract and promote gastric emptying 16.…”
Section: Discussionmentioning
confidence: 99%
“…Arrhythmia and sudden cardiac death have been associated with patients given IV domperidone in the setting of hypokalemia and, as a result, the IV formulation is no longer available [ 21 , 22 ]. Prolonged QTc has been associated with PO domperidone use although this may not lead to adverse events [ 23 ].…”
Section: Dopamine-2 (D2) Receptor Antagonists Domperidonementioning
confidence: 99%